2020
DOI: 10.1111/apm.13020
|View full text |Cite
|
Sign up to set email alerts
|

Cancer during HIV infection

Abstract: HIV+ persons have a significantly increased risk of cancer when compared to the general population. The excess cancer risk observed during HIV infection is particularly higher for infection‐related malignancies. Mechanisms underlying this remain unclear, but both HIV‐related and HIV‐unrelated factors have been postulated to play a role. Here, we (i) review newly published data on cancer burden in the setting of HIV infection with a focus on HIV‐related risk factors for cancer; (ii) discuss emerging data on can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…The higher risk of non-AIDS events found in our study could be explained by increased inflammation and immunoactivation, that have been already identified as potential mechanisms for both atherosclerosis [ 22 ] and malignancies [ 23 ] in PLWH. Thus, our findings bring to light the presence of those phenomena specifically in individuals with low CD4/CD8 ratio [ 8 ].…”
Section: Discussionsupporting
confidence: 55%
“…The higher risk of non-AIDS events found in our study could be explained by increased inflammation and immunoactivation, that have been already identified as potential mechanisms for both atherosclerosis [ 22 ] and malignancies [ 23 ] in PLWH. Thus, our findings bring to light the presence of those phenomena specifically in individuals with low CD4/CD8 ratio [ 8 ].…”
Section: Discussionsupporting
confidence: 55%
“…It is reported that approximately 85% of persons diagnosed with AIDS are aged 20-49 years (1981-2000) [42]. HIV can significantly damage the immune system, rendering patients prone to cancer and infection [43,44]. On one hand, patients diagnosed with HIV have a substantially higher risk of getting some types of cancer due to the compromised immune systems, including cervical invasive carcinoma, Kaposi's sarcoma, and various forms of lymphoma [45][46][47]; on the other hand, cancer patients are prone to opportunistic infections once they contract HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the mechanisms through which HIV infection increases cancer risk are not fully understood. HIV-induced immunodeficiency and co-infections with oncogenic viruses among people living with HIV (PLWH) are likely to play a key role [2,3]. Evidence for direct pro-oncogenic effects of HIV, especially in lymphomagenesis, has also emerged [4].…”
Section: Introductionmentioning
confidence: 99%